Integration of Quality Education System to Increase The Competitiveness of Graduates Pesantren - Sri Wahyuni; Pardiman Pardiman; Djoni Harijanto (Universitas Pesantren Kh Abdul Chalim Mojokerto, 2022)
This article reveals the contribution of the education quality system in increasing the competitiveness of Miftahul Midad Lumajang Islamic Boarding School graduates. Integration of the quality of the education system in order to increase the competitiveness of graduates Islamic boarding schools, with their salaf characteristics, continue to innovate continuously in the management of inputs, processes, and outputs to the outcome of the competitiveness of graduates. This type of research is qualitative with a case study approach, data obtained from interviews, observations, and documentation, then analyzed by condensing, displaying data, and drawing conclusions. The research findings show that the quality of the Miftahul Midad Lumajang Islamic Boarding School education system begins with the integration of visions between institutions under the auspices of the Miftahul Midad Lumajang Foundation. They were followed by setting goals and strategies for improving the academic quality of students through three models of quality development, namely coaching in the recitation, extracurricular activities, and activities in the pesantren environment.